REVITALISASI PASAR TRADISIONAL SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN SUMBAWA - Lily Suryani; Marisa Sutanty; S Suprianto (Pusat Riset dan Publikasi, 2023)
The purpose of this research was to determine the effect of traditional market revitalization on the welfare of the people in Sumbawa Regency. This research is a causal associative research with a quantitative approach. The type of data used is quantitative which is obtained directly from the research respondents. The respondents in this study were all traders in the Seketeng Sumbawa Besar traditional market, totaling 41 people. The data used in this study were collected using a research instrument in the form of a questionnaire. The data that has been collected is processed for analysis using simple linear regression analysis techniques, partial parameter hypothesis testing (t test), and determination coefficient test (R2). The results of this study indicate that the revitalization of the Seketeng traditional market has a positive and significant effect on the welfare of the people in Sumbawa Regency. The ability of the Seketeng traditional market revitalization variable in explaining variations in community welfare variables in Sumbawa Regency is 81.3%, while the remaining 18.7% is influenced by other variables outside this research model, such as economic growth, income per capita, human development index ( HDI), and unemployment.